Acanthistius patachonicus, Patagonian Grouper - Irigoyen, Alejo Joaquin (2020)
This rocky reef species has a relatively small range from southern Brazil to central Argentina. It is long- lived and the estimated generation length is 28.5 years. Large commercial fisheries targeted spawning aggregations of this species in the 1980s and 1990s until abundance steeply declined to the point where the market was no longer viable and at least four large areas where spawning aggregations were heavily depleted. Currently, it continues to be targeted by artisanal and industrial fisheries. The implementation of effective fishing area closures, both permanent and seasonal, in the El Rincón area is considered to provide a high level of protection for half of the global population of this species. According to fisher interviews, some level of population decline occurred within the past 40 years, or over a little more than one generation length ago. The lack of fisheries data, including a stock assessment, and the low level of understanding of the status of historical and current spawning aggregations prevents the estimation of percent population decline at this time. A secondary threat may be the reduction of habitat quality due to the invasive alga Undaria pinnatifida on shallow reefs, which has spread through much of its range. It is listed as Data Deficient with a strong recommendation to improve fishery monitoring and to conduct studies on spawning aggregations.